2017
DOI: 10.1007/s11606-017-3993-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department-Initiated Buprenorphine for Opioid Dependence with Continuation in Primary Care: Outcomes During and After Intervention

Abstract: ED-initiated buprenorphine was associated with increased engagement in addiction treatment and reduced illicit opioid use during the 2-month interval when buprenorphine was continued in primary care. Outcomes at 6 and 12 months were comparable across all groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
147
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(153 citation statements)
references
References 20 publications
5
147
1
Order By: Relevance
“…11,12 A multidisciplinary and multidimentional approach not only for HCV care but also for opioid substitution therapy might significantly improve linkage-to-care rate. 11,13 Regarding limitations, this is a single institution study with a small number of seroconversions. In addition, our estimates of incidence are based only on tests within our health system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…11,12 A multidisciplinary and multidimentional approach not only for HCV care but also for opioid substitution therapy might significantly improve linkage-to-care rate. 11,13 Regarding limitations, this is a single institution study with a small number of seroconversions. In addition, our estimates of incidence are based only on tests within our health system.…”
Section: Discussionmentioning
confidence: 98%
“…Successfully linking newly diagnosed (including incident) HCV‐infected ED patients for HCV care at specialty clinic has been widely recognized as one of the most critical steps for eliminating HCV in the community; challenges remain, however, as linkage rate from other ED are in the low 30s . A multidisciplinary and multidimentional approach not only for HCV care but also for opioid substitution therapy might significantly improve linkage‐to‐care rate …”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that ED-initiated buprenorphine increases subsequent engagement in addiction treatment and reduces illicit opioid use. 27 Devoting more health resources to initiating evidence-based ED-based treatments for patients with opioid use disorder in health systems, including ED-initiated buprenorphine and referral to SUD treatment, 27 may be a step toward improving health outcomes and reducing high SUD-related ED visits among patients with opioid use disorder.…”
Section: Discussionmentioning
confidence: 99%
“…From an economic perspective, Horn et al (2016) found case management to be economically effective in a cohort of high-cost medically complex patients in New Mexico. Additionally, ED-initiated buprenorphine treatment has been found to significantly increase engagement in addiction treatment and reduce illicit opioid use (D’Onofrio et al, 2017; D’Onofrio et al, 2015). Also, it may be the case that more intensive interventions may be required to benefit individuals with serious drug use disorders.…”
Section: Discussionmentioning
confidence: 99%